2012
DOI: 10.2174/156802612805219978
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidases: The Biochemistry of the Proteins As Targets in Medicinal Chemistry and Drug Discovery

Abstract: Monoamine oxidase (MAO, EC.1.4.3.4) has been a drug target for 60 years, with the primary rationale of developing drugs to treat neuropsychiatric disorders. The biological importance of MAO is to regulate amine levels is the brain and to metabolize amines and drugs in the periphery. This review of the biochemistry of MAO A and MAO B describes the functional properties of the two enzymes integrated with knowledge of the structures of the many MAOinhibitor complexes published in the last 10 years. The analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 251 publications
(370 reference statements)
0
45
0
Order By: Relevance
“…15 Moreover, we have also shown that the protonation state of Lys296 does not have an effect on the hydride transfer reaction in MAO B, which is consistent with the proposed function of the lysine as stabilizing the superoxide required for the regeneration of the enzyme. In conjunction with additional experimental and computational work, the data presented here improve the understanding of mechanism of the catalytic activity and irreversible inhibition of MAO B, which can allow for the design of novel and improved MAO B inhibitors for antiparkinsonian and neuroprotective use …”
Section: Resultsmentioning
confidence: 92%
“…15 Moreover, we have also shown that the protonation state of Lys296 does not have an effect on the hydride transfer reaction in MAO B, which is consistent with the proposed function of the lysine as stabilizing the superoxide required for the regeneration of the enzyme. In conjunction with additional experimental and computational work, the data presented here improve the understanding of mechanism of the catalytic activity and irreversible inhibition of MAO B, which can allow for the design of novel and improved MAO B inhibitors for antiparkinsonian and neuroprotective use …”
Section: Resultsmentioning
confidence: 92%
“…[63,64] amines occurring in food, such as tyramine. In the brain, MAO B mainly metabolises dopamine, while MAO A predominantly metabolizes serotonin, which is why these two isoforms are key pharmaceutical targets in alleviating the symptoms of Parkinson's disease and depression, respectively [87,88]. However, MAO selectivity is quite poor since, for example, MAO B also decomposes serotonin only five times slower than dopamine [89].…”
Section: Hydrogen Peroxide-related Enzymesmentioning
confidence: 99%
“…In humans MAO A is predominantly found in adrenergic, catecholaminergic and dopaminergic neurons and deactivates serotonin, dopamine, norepinephrine and epinephrine. Human MAO B participates in dopamine degradation and is mainly expressed in serotonergic neurons and glial cells1415. Therefore, MAO inhibitors are frequently investigated for treatment of depression and Parkinson’s disease16.…”
mentioning
confidence: 99%